Criação de um modelo geoespacial para seleção de áreas visando a implantação de um aterro sanitário - Noberto, Camila Carvalho (Universidade Federal Rural do Semi-Árido, 2018)
The proper disposal of solid waste is of great socio-environmental importance. Currently, a disposal in landfills is a safer way to minimize, mainly, the environmental impacts. And, the costs to implement areas like these are big. Aiming at the intermunicipal consortium, the work is designed to generate a geospatial model for capturing areas in a sanitary landfill in the microregion Chapada do Apodi, in the state of Rio Grande do Norte. For this, a sample of 60 species was distributed in this region; and based on five criteria, such as the relevant ones, was achieved as assessments. From the use of the QGis program, it was possible to process, transform and analyze the data. Soon after, the data were tabulated, and in the end, each site was prepared with a note, which gave rise to a balance of the payment scores in each criterion. Based on this information, we were able to find an equation that represented the percentage of scores. These data were inserted in the software, making possible the interpolation of the values, allowing to generate a geospatial model that evaluated the area as a whole. It is concluded that 67% of the microregion area presented greater susceptibility, being these, in general, located more to the north of the region. With this instrument, one can verify the use of geoprocessing tools as a geospatial model, based on an analysis of several parameters, for the selection of areas for the several implementation.
Monografia
Keywords: Consórcio municipal; Geoprocessamento; Resíduos sólidos; Multicritérios; Municipal consortium; Geoprocessing; Multiple criteria; Solid waste; ENGENHARIAS::ENGENHARIA CIVIL